FORMATION OF COMMUNICATIVE COMPETENCE OF THE FUTURE TEACHER IN THE EDUCATIONAL ENVIRONMENT OF THE INSTITUTION OF HIGHER EDUCATION - Малишева, Л.С.; Сорокіна, С.І. (Modern engineering and innovative technologies, 2024)
The problem of forming students’ communicative competence is one of the current pedagogical problems, the solution of which contributes to the development and strengthening of the economic state of society and the state as a whole. In accordance with the